2012
DOI: 10.1200/jco.2011.38.5674
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Brain Activation During Working Memory Processing Associated With Breast Cancer and Treatment: A Prospective Functional Magnetic Resonance Imaging Study

Abstract: A B S T R A C T PurposeTo prospectively examine alterations in working memory (WM) -associated brain activation related to breast cancer and treatment by using functional magnetic resonance imaging. Patients and MethodsPatients treated with chemotherapy (CTxϩ; n ϭ 16) or without chemotherapy (CTxϪ; n ϭ 12) and healthy controls (n ϭ 15) were scanned during an n-back task at baseline (after surgery but before radiation, chemotherapy, and/or antiestrogen treatment), 1 month after completion of chemotherapy (M1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
244
4
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(276 citation statements)
references
References 58 publications
22
244
4
6
Order By: Relevance
“…These previous results in combination with our present findings suggest that there are likely region-and/or network-specific effects of cancer and its treatments. For example, C− may be more associated with prefrontal network disruption compared with DMN (11,32,35). However, it is also possible that our sample sizes were too small and/or the cross-sectional nature of the present study prevented us from detecting differences in DMN in the C− group.…”
Section: Discussioncontrasting
confidence: 45%
“…These previous results in combination with our present findings suggest that there are likely region-and/or network-specific effects of cancer and its treatments. For example, C− may be more associated with prefrontal network disruption compared with DMN (11,32,35). However, it is also possible that our sample sizes were too small and/or the cross-sectional nature of the present study prevented us from detecting differences in DMN in the C− group.…”
Section: Discussioncontrasting
confidence: 45%
“…In line with the findings from the animal work reported above, diffusion tensor imaging (DTI) studies have found chemotherapy-related reductions of white matter integrity that correlated with cognitive performance [30]. A prospective DTI study Paradigms included verbal long-term memory [37,38], verbal working memory [39,40], and tasks requiring rule testing or planning, both involving prefrontal cortex [41,42]. Activation …”
Section: Manysupporting
confidence: 54%
“…11 Conversely, in a study investigating women with breast cancer receiving Lupron and healthy women 12 no significant differences were found between groups in working memory irrespective of task complexity. However, in another study while reaction times and task performance accuracy in working memory did not differ between breast cancer survivors and non-cancer controls, 13 there were significant differences in frontal lobe activation in breast cancer survivors.…”
Section: Introductionmentioning
confidence: 81%